2006
DOI: 10.1080/10196780600841399
|View full text |Cite
|
Sign up to set email alerts
|

Gender Salience in Electronic Negotiations

Abstract: There is ample empirical evidence for the impact of gender in face-to-face negotiations. In electronic negotiations, the use of electronic negotiation support systems (eNS) implies important differences to face-to-face communication settings: (1) eNSs permit among other functions, revising, storing, processing, and transmitting information and (2) Computer-mediated communication reduces the transmission of interpersonal and social context cues. In this study, we use a controlled laboratory experiment to analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Further, women tend to focus their communication on maintaining good intra-team relationships (Gilligan, 1992;Maznevski, 1994), often through consensus-building (Elsass & Graves, 1997;Hess, Fuller, & Mathew, 2006) and the creation of joint gains (Koeszegi, Pesendorfer, & Stolz 2006).…”
Section: Gender Diversity and Text Communication Vs Ftf Communicationmentioning
confidence: 99%
“…Further, women tend to focus their communication on maintaining good intra-team relationships (Gilligan, 1992;Maznevski, 1994), often through consensus-building (Elsass & Graves, 1997;Hess, Fuller, & Mathew, 2006) and the creation of joint gains (Koeszegi, Pesendorfer, & Stolz 2006).…”
Section: Gender Diversity and Text Communication Vs Ftf Communicationmentioning
confidence: 99%
“…In these cases, men fight and take on foes that cause harm to others who are "defenseless" or weaker and show tenderness and protection to those they consider subordinate. We find these trends in the literature where men become more cooperative when negotiating with women versus negotiating with other males since perhaps men are generally socialized to take care of women (Calhoun and Smith, 1999;Koeszegi et al, 2006;Vigen, 2007). While there have been many studies emphasizing the differences in cooperative-competitive orientation between men and women, there is a body of evidence showing that these differences are non-existent or insignificant at best (Lewicki et al, 1994).…”
Section: Gender and Cooperative-competitive Orientationmentioning
confidence: 60%
“…This encompasses "really talking" (Kolb and Coolidge, 1991, p. 266) and carefully listening to understand both extrinsic and intrinsic needs of the other party. Supporting this proposition, Koeszegi et al (2006) found that women's negotiation behavior is not affected by whether they know their counterpart or not. However, this pattern is not found in men.…”
Section: Gender and Negotiation Behaviormentioning
confidence: 73%
“…Secondly, it has to be considered that other potential influences such as gender e.g., (Koeszegi, Pesendorfer, and Stolz, 2006), negotiator's preferences for specific styles e.g., (Kilmann and Thomas, 1977), cognitive biases e.g., (Neale and Bazerman, 1992), system and communication mode characteristics e.g., etc. Although we have conducted a pilot study with follow-up-interviews to make the simulation as realistic as possible, there are limits in laboratory experiments.…”
Section: Limitations and Opportunities For Further Researchmentioning
confidence: 99%